1997
DOI: 10.2527/1997.7571861x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interrelationship between zinc oxide and copper sulfate on growth performance of early-weaned pigs.

Abstract: We conducted four experiments to examine the effects of adding zinc oxide (ZnO) and(or) copper sulfate (CuSO4) to diets for weanling pigs. In Exp. 1 and 2, weanling pigs (initially 5.3 kg and 19 +/- 2 d of age) were fed diets containing 250 ppm of added Cu (CuSO4) and either 110 or 3,110 ppm of added. Zn (ZnO). No differences (P > .10) were observed in either experiment for ADG, ADFI, or feed efficiency (G:F). In Exp. 3,240 pigs (initially 4.45 kg and 15 +/- 2 d of age) were used to determine the interactive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
4
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 11 publications
8
72
4
5
Order By: Relevance
“…Limited study is available to document or explain the interactions between TBZC and CuSO 4 in weanling piglets. Smith et al (1997) found an interaction between ZnO and CuSO 4 for ADG from d 14 to 28 after weaning. A regional study conducted by Hill et al (2000) found an interaction between Zn (ZnO) and Cu (CuSO 4 ) for growth performance, and responses to Zn and Cu were independent and not additive in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited study is available to document or explain the interactions between TBZC and CuSO 4 in weanling piglets. Smith et al (1997) found an interaction between ZnO and CuSO 4 for ADG from d 14 to 28 after weaning. A regional study conducted by Hill et al (2000) found an interaction between Zn (ZnO) and Cu (CuSO 4 ) for growth performance, and responses to Zn and Cu were independent and not additive in the current experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding 250 mg/kg Cu from CuSO 4 improved growth performance of weanling piglets (Armstrong et al, 2004). Previous research indicated that there was an interaction between high level of zinc oxide (ZnO) and CuSO 4 , but additive responses to growth-promoting were not observed (Smith et al, 1997;Hill et al, 2000). However, recently research reported that organic copper and ZnO had additive benefits effects on piglet's performance (Pettigrew and Perez-Mendoza, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have found additive effects of Zn and Cu in weanling pigs (Smith et al, 1997;Hill et al, 2000). Nevertheless, there has been increased interest in the use of organic chelated mineral complexes as mineral sources for weanling pigs because of their higher potential bioavailability when compared to minerals from inorganic sources.…”
Section: Discussionmentioning
confidence: 99%
“…As it has been shown that the continuous use of antibiotics as growth promoters provoke the retention in animal tissues and that the human consumption of such animal products would potentially increase processes of antibiotic resistance, movements of social pressure towards food security were claiming for a strict control and against their use in animal feeding, reaching the banning of using antibiotics as growth promoters from 2006 in the European Community (CE 1831(CE /2003. In other way, the use of some trace elements such as zinc and copper, that have been systematically included as growth promoters in diets for weaned piglets because of their beneficial role in pig health status (Hahn & Baker 1993;Smith et al, 1997) have been also restricted to those levels that satisfy the metabolic needs of animals because of both their retention in animal tissues and environmental hazard. The addition of high doses of zinc (from 2500 to 3500 ppm, as zinc oxide) or copper (from 150 to 250 ppm, as copper sulphate) modulates the microbial status of the digestive tract and reduce the incidence of post-weaning diarrhoea (Jensen-Waern et al, 1998;Broom et al, 2006), generally promoting increases in productive performances (Hill et al, 2000;Case & Carlson, 2002).…”
mentioning
confidence: 99%